Ventilation Structure Improvement of Air-cooled Induction Motor Using Multiphysics Simulations - Yujiao Zhang; Xiongfeng Huang; Tao Huang; Jiangjun Ruan; Xiaowen Wu Xiaowen Wu (Universitas Ahmad Dahlan, 2012)
Optimal design of large induction motor is a process that involves electrical and mechanical skills as well as thermal and fluid dynamic skills. For recent machine layouts, one cannot rely on standard analysis methods. In multiphysics simulations which are done by weak coupling finite-element method, rotation boundary values on interface between air gap and rotor cannot be applied directly for fluid-dynamical analysis. A novel multi-component fluid method is proposed to deal with the influence of rotor rotation upon the air convection. This paper investigates a 3-D multi-physics simulation used in simulation of temperature distribution in air-cooled induction motor. The temperature rise in motor is due to Joule’s losses in stator windings and the induced eddy current in squirrel cages, and heat dissipation by air convection and solid conduction. The Joule’s losses calculated by 3-D eddy-current field analysis are used as the input for the thermal field analysis, which deeply depends on accurate air fluid field analysis. Through the coupled-field calculation, we proposed a new ventilation structure of a 15-phase motor to improve the cooling performance.